Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Māori Political Representation: A Case for Change - Mahuta, Robert (Maori Representation in Parliament, 1982)
Keywords: mana motuhake; māori electorates; māori seats; population; voting

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Effecting Change Through Electoral Politics: Cutlural Identity and the Māori Franchise - Sullivan, Ann (Journal of the Polynesian Society, 2012)
Keywords: economic development; māori seats; social development; tino rangatiratanga; voting

The predictors of Māori electoral roll choice and knowledge: rangatahi Māori voter enrolment in a representative New Zealand youth survey - Greaves, Lara M.; Hayward, Janine; Barnett, Daniel; Crengle, Sue; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2023)
Every five years and when initially enrolling to vote, Māori have the choice between the Māori roll or the general roll. Research has explored the predictors of roll choice for older adults, but this paper presents the first exploration of roll choice for rangatahi Māori (Māori youth; aged 13–18), and the predictors of rangatahi not understanding the difference between rolls. We draw on Māori data (n = 1528) from Youth19 which surveyed students from a random sample of schools from Tai Tokerau, Tāmaki Makaurau, and Waikato. We find those Māori who also identify as Pākehā (New Zealand European) are less likely to opt for the Māori roll, but those who know their Iwi, are comfortable in Māori social surroundings, feel a spiritual connection to land and the presence of their ancestors in their lives, or feel the drive to be respected as Indigenous, are more likely to choose the Māori roll. Older rangatahi are more likely to say they understand the question, as are those with study plans post-secondary school, and who say they are comfortable in Māori social settings. These results contribute to a body of knowledge valuable for those seeking to increase voter enrolment and enrolment on the Māori roll.Glossary of Māori words: Hapū: kinship group, generally smaller than Iwi; sometimes translated to sub-tribe; hui: meeting; Iwi: broader tribal unit or grouping; nation; kaitiaki: guardian, steward, trustee; kanohi-ki-te-kanohi: face to face/in person; kapa haka: Māori performing arts; traditional performance; Kura Kaupapa Māori: Māori language/Māori medium schools; mana whenua: Māori group(s) who have authority, power, or rights over a certain area of land; marae: meeting house and the area surrounding it; mātauranga Māori: Māori ways of knowing/knowledge; Pākehā: New Zealanders of European descent; rangatahi: youth; rohe: area, region; tangata whenua: Indigenous peoples of Aotearoa New Zealand; people(s) of the land; te reo Māori: the Māori language; te Tiriti o Waitangi: the Māori language version of the Treaty of Waitangi; tīpuna/tupuna: ancestors; waka ama: canoe sport; wānanga: meetings for discussion, deliberation, forums; whanau: family, extended family, or family-like group; whanaungatanga relationship, kinship, sense of family-like connections between people.
Keywords: māori roll; political participation; rangatahi; tūpuna; voter enrolment; voting

Dynamic and Interesting Events: The Nineteenth-Century Māori Elections - Warbrick, Paerau (New Zealand Journal of History, 2019)
The article discusses the history of the political participation of the Maori people of New Zealand in the 19th century which started with the creation of the Maori seats of Parliament under the Maori Representation Act 1867 (MRA). Topics discussed include the incorporation of MRA into the Electoral Act of 1893, the history of their voting rights, practices and election participation, and the issue of giving fair representation to Maori in the House of Parliament in 1862.
Keywords: government relations; history; māori seats; voting

Comparative Constitutional Law and Indigenous Peoples: Canada, New Zealand and the USA - Claire Charters (Comparative Constitutional Law, 2011)
Keywords: constitution; crown law; crown policy; kāwanatanga; voting

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

The Māori Electoral Option: How can trends in roll choices be explained? - Bargh, Maria (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
The Mäori Electoral Option is a period of 4 months, every 5 years, when Mäori electors can choose whether to be on the Mäori or the General Electoral Roll. The outcome of the Mäori Electoral Option is a key factor in determining the number of Mäori seats in the New Zealand Parliament. The Electoral Commission estimates that approximately 6,000 Mäori voters each year request to change electoral roll, but in 2017 over 19,000 voters applied to change. Why were so many more Mäori wanting to change and why did they not know they could only change during the Mäori Electoral Option held every 5 years? The following year, the 2018 Mäori Electoral Option saw the first net increase of Mäori changing to the general roll since 1996. This article uses data gathered from the results of Mäori Electoral Options 1991–2018, an anonymous survey, and evaluations of Mäori Electoral Option campaigns to consider how the shifting trends in roll choices might be explained.
Keywords: elections; kāwanatanga; māori electorates; māori seats; voting

Multiple sites of Māori political participation - Bargh, Maria (Australian Journal of Political Science, 2013)
This article examines what might be included in a definition of Māori political participation that moves beyond a predominant focus on voting in New Zealand general elections. I suggest that the proliferation of Māori governance organisations in recent years means that Māori participation within these organisations must also be considered as part of wider political participation. In addition, I argue that Māori engagement with local authorities deserves further close examination to explore the multiple ways in which political participation occurs. Using a broader definition of Māori political participation and highlighting its many facets indicate that Māori engage in more varied ways in New Zealand politics than previously recognised
Keywords: kāwanatanga; local government; local politics; political participation; tino rangatiratanga; voting

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting

Identity and demographics predict voter enrolment on the Māori electoral roll: Findings from a national sample - Greaves, Lara; Osborne, Danny (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
Keywords: identity; māori electorates; voting; voting enrolment

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting

Challenges on the path to Treaty-based Local Government relationships - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
In this article I examine some of the challenges for Māori and Local Government on the path to Treaty-based Local Government relationships. I suggest significant challenges exist in three core areas. The first relates to the attitudes towards the ideas of Treaty-based Local Government and evident in common terminology which has a narrow focus on the identity of Māori as ‘representatives' rather than ‘Treaty partners’. The second area of challenge is in having Māori wards/constituencies established which, when they are established, are symbolically the beginnings of an acknowledgment of Treaty obligations and relationships. The third challenge is the lack of good data which limits understandings of Māori involvement in Local Government. In the second part of the article I ask whether any specific challenges can be seen that might impact on Treaty-based relationships in regard to Māori involvement as candidates and voters in Local Government elections.
Keywords: elections; local elections; local government; māori electorates; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty-based relationships; voting